Net neutrality and its influence on the competetiveness of web-based services - Trnka, Krzysztof (Management and Administration Journal, 2019)
Access to knowledge and technology is necessary for the proper functioning of a competitive economy. The fastest and most efficient way to obtain and relay information is through the use of electronic media, particularly the Internet. Therefore nation-states should take steps to ensure the free flow of information and fair access to it through the Internet. One of the means to achieve this goal is net neutrality – a regulation, mandating the equal treatment of all sites, platforms and services available on the Web. For the purposes of this paper, achievements of the school of law and economics have been utilized, the behavioural method in particular. The method is used to examine legal rules through the prism of expected social response, i.e. behaviour of addressees of the rule being analyzed, with the assumption that they are guided by a rational desire to fulfill their own economic interests to the fullest extent possible. The author reviewed the arguments presented in scholarly literature, put forward by representatives of economic, legal and IT sciences, both opponents, as well as advocates of net neutrality. An emphasis was put on arguments taking the traits of the Internet as a two-sided market into account. The critical analysis of the aforementioned arguments has led the author to the conclusion, that abandoning the principle of net neutrality creates conditions for companies that are favoured by Internet Service Providers to become more competitive in an undeserved manner. This increase in competitiveness would not involve a higher quality of services or a lower price, so it would be detrimental to consumers. As a consequence, new monopolies may be created or existing ones may become more entrenched. Net neutrality was on the books in the USA from 2015 to 2017, based on a regulation issued by the FCC. This regulation was recently repealed